The Effect of My Daily Book Movie on Strengthening Character Education of Madrasah Ibtidaiyah Students - Liviani, Ratna; Prabowo, Mei (Fakultas Tarbiyah dan Ilmu Keguruan Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2023)
Film is one of the educational means to provide learning to children indirectly through characters and stories in films. One of the films that can be a learning tool is the film My Diary. The purpose of this study was to determine the influence of a film entitled Buku Harianku on the strengthening character education of Elementary Islamic School students in West Jakarta. This research uses an experimental method. The sample of this study used a random sampling technique. The experimental sample in this study was MIS grade V students Hidayatul Istiqomah. With experimental classes are classes V C and V D while the control class is class V A and V B. Data collected using questionnaires. The character of the students tested includes religious, nationalist, independent, mutual aid, and integrity values. Based on the results of research that has been done, it is known that the film My Diary has an influence on the character of students with a magnitude of 48% and has a significant effect.